A study of two facades for a sustainable built environment - Hj Mohd Ariffin, Noor Aziah; Phoo, Pwint Thu Aung (2013)
Energy use and the associated carbon dioxide emissions, has been rising rapidly over the past few decades and about 40% of the global energy consumption is associated with the construction sector. Of late many measures have been stepped up to curb the excessive use of energy in buildings which resulted in many energy rating and benchmarking efforts by many countries. At present Malaysia’s building energy is rated by the Green Building Index (GBI) and one of the criteria to reduce a building’s carbon footprint lies in the ability of facades to moderate and optimize its immediate environment. A building’s façade is supposed to play an important role in the overall energy performance of buildings apart from its aesthetic and visual impacts. This study looked at the impact of two different building facades: the double skin façade (DSF) and the green façade system (GFS) in mitigating temperature and consequently the energy use in buildings. The two different types of facades are scrutinized in detail to ascertain their performance on energy efficiency efforts. This study will present the preliminary findings of data monitoring on thermal performance of both types of facades as a means for energy savings in improving the sustainable built environment, as also advocated in all Islamic teachings. The study found that both facades are effective in reducing temperatures of immediate areas to the skins indicating potential comfort and energy performances.